Analysis of Nutritional Quality of Black Fungus Cultivated with Corn Stalks - Hongwei Yao; Yang Liu; Zheng Feei Ma; Hongxia Zhang; Tingting Fu; Zunqiang Li; Yuanjing Li; Wei Hu; Shuchang Han; Fengchen Zhao; Hongjun Wu; Xueyi Zhang (Journal of Food Quality)
Black fungus is a homologous fungus of medicine and food. Its nutrient content determines the health value, and the accumulation of nutrients is easily affected by the substitute materials. The aim of this study was to analyze the effect of corn stalks as a cultivation substitution material for sawdust on macronutrients, micronutrients, and functional components of black fungus. The results reported that corn stalks could significantly increase the content of ash, protein, copper, and iron in black fungus, but reduce the content of zinc, magnesium, manganese, and colloidal substances; corn stalks had less effect on melanin and polyphenols; its effect on water, total sugar, reducing sugar, crude fiber, and total flavonoids was insignificant. Therefore, the study provided a theoretical basis for the cultivation of black fungus with corn stalks.